Colour pattern variation forms local background matching camouflage in a leaf‐mimicking toad. (9th September 2021) - Barnett, James B.; Michalis, Constantine; Scott‐Samuel, Nicholas E.; Cuthill, Innes C.
Abstract: Optimal camouflage can, in principle, be relatively easily achieved in simple, homogeneous, environments where backgrounds always have the same colour, brightness and patterning. Natural environments are, however, rarely homogenous, and species often find themselves viewed against varied backgrounds where the task of concealment is more challenging. One result of variable backgrounds is the evolution of intraspecific phenotypic variation which may either be generalized, with multiple similarly cryptic patterns, or specialized, with each discrete colour form maximizing concealment against a single component of the background. We investigated the role of phenotypic variation in a highly variable population of the Neotropical toad Rhinella margaritifera using visual modelling and a computer‐based detection task. We found that phenotypic variation was not divided into discrete colour morphs, and all toads were well camouflaged against the forest floor. However, although the whole population may appear to consist of random samples from the background, the toads were a particularly close match to the leaf litter, suggesting that they masquerade as dead leaves, which are themselves variable. Furthermore, rather than each colour form being equally effective against a single background, each toad was specialized towards its own particular local surroundings, as suggested by a specialist strategy. Taken together, these data highlight the importance of background matching to a nominally masquerading species, as well as how habitat heterogeneity at multiple spatial scales may affect the evolution of camouflage and phenotypic variation. Abstract : Colour variation is common in camouflaged species. Variation may be continuous or discrete, with different patterns found in the same, or geographically distinct, populations. Sometimes variation is linked to microhabitat specialization, sometimes to the advantages of having a rare pattern (with which predators aren't familiar). In a Neotropical toad, we found that continuous colour pattern variation matches the local leaf‐litter, such that the toads benefit from both microhabitat‐specific camouflage and mimicking dead leaves.